Strategizing inclusivity in teaching diverse learners through community of practice in higher education - Awang Hashim, Rosna; Kaur, Amrita; Valdez, Nena P. (2017)
Purpose - As the classrooms in higher education are growing increasingly diverse, it is imperative that higher education practitioners build a responsive learning environment for diverse learners to optimize their potential without getting threatened or feeling alienated due to differences in their backgrounds and capabilities. The ability to embrace inclusive practice is a way forward to acknowledge and address the complexities of existing classrooms in higher education.Continuing professional development programmes (CPD) are central to such strategic approaches that equip educators with essential knowledge and skills to handle diversity related issues, achieve equality and increase participation by students (May & Bridger, 2010). Considering the fact that context is central to strategizing diversity initiatives, the present study initiated a Community of Practice (CoP) of higher education practitioners in a public university to achieve an in-depth understanding of the nature of diversity within the institution and to facilitate a process through which members of the community can strategize inclusivity through a proactive and iterative approach.Therefore, in the present study we employ CoP Practice as the theoretical lens and a methodological tool to understand inclusion in a particular institutional context and devise strategies through a series of non-participative observations, reflective journals, and focus groups. The research question that guided the study was: What strategies do higher education practitioners devise for their inclusive practices in response to the challenges through a CoP.Methodology - In this study, we adopted a qualitative research paradigm to understand how higher education practitioners perceive diversity and its related challenges in their classrooms and what inclusive strategies do they devise through a CoP. Qualitative inquiry was deemed appropriate for in-depth exploration of the research question and understanding the culture of a particular setting from the insider’s perspective (Ary, Jacobs, Razavieh, & Sorenson, 2009).The CoP lasted for seven months whereby a series of interface discussions, sharing of reflections, participants’ narratives, and direct experiences took place and inputs from participant’s peer or critical friends were generated. There were multiple data sources in this study that generated the information. The primary source of data was non-participative observation by the researchers during the CoP sessions and participants reflections.The sessions were audio and video taped which later were transcribed verbatim.The second source of data was reflective writing submitted by the participants. The detail on this source is elaborated in data collection procedure. Purposive sampling strategy was employed in selecting the participants as the study was seeking a platform to build a community of higher education practitioners who have experiences with students’ diversity in higher education (Patton, 2002). Nine academicians (6 males and 3 females) who emerged from natural retention along the iterative cycles on CoP participation were considered as participants.The data was explored by reading and rereading at preliminary stages to obtain clarity (Denzin, 2005) and through repetitive readings the data was coded for two prime categories, namely, challenges and strategies. Later, according to the prevalence and frequency count (McMillan & Schumacher, 2001) the strategies were analyzed against the challenges reported and finally the strategies were reduced into major themes.Findings - After the data reduction process, three major themes emerged that report the inclusive strategies conceived by the participants.The themes were - Inclusive/differentiated assessment, Motivation and Goal Strategies, and inclusive pedagogy. The theme Inclusive/differentiated assessment suggested that creating differentiated assessment that are inclusive in nature and can provide equal opportunity to every student to participate was a way forward. The participants collectively agreed on allowing flexibility in terms of preferred language and mode to give equitable opportunity to all students. The theme Motivation and Goal Strategies revealed that students were found to be diverse in their goals for learning, hence a variety of motivational strategies such as including students’ voice, providing them a clear rationale for studying and fostering relatedness were deemed suitable to address those differences. The final theme, inclusive pedagogy suggests a variety of accommodations to be made in pedagogy such as integrating technology,adopting culturally responsive material and initiating collaborative learning to address students’ differences.